Design of Oxytocin Massage Vest for Breastfeeding Mothers Based on Arduino Uno: Rancang Bangun Rompi Pijat Oksitosin pada Ibu Menyusui Berbasis Arduino Uno - Rahajeng, Tassya; Nugroho, Eko; Aprilia, Septi; Dewi, Wiwik Puspita (RADIANT: Journal of Applied, Social, and Education Studies, 2025)
Optimal breast milk (ASI) production is essential for infant health and the well-being of breastfeeding mothers. One innovative approach to support this is the use of an electromedical device in the form of an oxytocin massage vest based on a microcontroller. This study aims to design and develop a prototype of an Arduino Uno–based oxytocin massage vest that provides automatic stimulation at specific points along the spine of breastfeeding mothers. The research employed a Research and Development (R&D) approach using a one-group pre-test post-test design. A total of 10 postpartum mothers (over 6 months) participated in the trial. The test results showed a significant increase in breast milk volume, from an average of 18.8 ml to 35.4 ml after using the device. The motor speed reached 22.0 rpm, with a 0% error in timing accuracy and a 0.5% deviation in voltage, all within acceptable tolerances. Although the device demonstrated high effectiveness, limitations such as a small number of respondents and fixed massage point designs were noted for future improvement. This massage vest has the potential to be a practical and innovative solution for enhancing breastfeeding success through consistent and measurable oxytocin stimulation.